Determinants of digital financial exclusion as a barrier to the adoption of mobile banking services in Poland - Solarz, Małgorzata; Adamek, Jacek (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: the contemporary phenomenon of financial exclusion, in the sphere of its reasons, consequences and activities aimed at its reduction can be connected, e.g., with using new technologies and financial innovations. The new dimension of such exclusion is created by the digital financial exclusion developed through a diverse set of behavioral, environmental and demographic factors. Their identification and analysis has become an essential activity influencing, e.g., the effectiveness of selective choice and application of proper tools to reduce this exclusion. Aim: identification and assessment of the determinants related to digital financial exclusion as a barrier in the adoption of mobile banking services, considered from the perspective of their impact on the segmentation of the analysed population. Results: the ranking, identified by the authors, regarding the importance of predictors indicated that the dependent variable — Y (i.e. people who have an online bank account classified based on the mobile forms of its use) is most influenced by the generation factor — X4 (1.0), followed by: personal innovativeness — X2 (0.92), digital skills — X1 (0.90) and the perceived risks of new technologies — X3 (0.66).